Financial Sector And Blockchain Technology: Challenges And Applications (Journal of Pharmaceutical Negative Results, 2023)
The present study aims to provide a holistic understanding of the multidimensional applications of blockchain in the global finance sector. This paper is an attempt to highlight the Strengths, Weaknesses, Opportunities, and Threats to blockchain technology in financial services. SWOT analysis has been conducted by critical investigation of relevant extant literature in the context of peer-reviewed international journals and industry reports. The findings of the study reveal that limited contributions by blockchain technology have been made in the financial sector. It has untapped potential to contribute to the development of financial services. The risk of blockchain technology can be further minimized and trust can be built in the mindset of the government regulator by implementing strict regulation while adopting blockchain technology. The findings of the paper will stimulate future research in the multidimensional adoption of blockchain technology in the financial sector.